Outline [large type] - Cusk, Rachel, 1967- (Thorndike Press large print basic, 2015)
"Rachel Cusk's Outline is a novel in ten conversations. Spare and stark, it follows a novelist teaching a course in creative writing during an oppressively hot summer in Athens. She leads her students in storytelling exercises. She meets other visiting writers for dinners and discourse. She goes swimming with an elderly Greek bachelor. The people she encounters speak, volubly, about themselves: their fantasies, anxieties, pet theories, regrets, and longings. And through these disclosures, a portrait of the narrator is drawn by contrast, a portrait of a woman learning to face a great loss. Outline is Cusk's finest work yet, and one of the most startling, brilliant, original novels of recent years"--